Reviving the grasp: a case report on a pioneering approach to managing crush syndrome and unveiling the occult compartment syndrome - Kee, Hoe Teong; Jaapar, Mohd Shahril; Arumugam, Manohar; Mohamed Saaid, Firdati; Looi, Collin; Che-Hamzah, Fahrudin (Springer, 2024)
A crush injury results directly from a crushing force, while crush syndrome, or traumatic rhabdomyolysis, manifests as systemic consequences stemming from the breakdown of muscle cells. Hand crush injuries present intricate challenges involving damage to multiple structures, tissue loss, and potential digit amputation, often caused by high-energy trauma. Each case demands a unique management plan, with the critical decision between limb salvage and amputation. Early intervention to restore vascularity is pivotal for preserving hand function. The complexity is heightened by the occult compartment syndrome, characterized by increased pressure causing neurovascular compromise without external signs. A patient with an insensate limb due to ipsilateral pan brachial plexus injury (BPI) adds an additional layer of complexity to the management journey, emphasizing the need for a multidisciplinary approach. This unique case underscores the importance of prioritizing reconstruction, identifying crush and occult compartment syndrome, and employing a strategic, decisive approach that includes various surgical techniques for optimal outcomes in complex hand injuries.